Does the adoption of soil carbon enhancing practices pay off? Evidence on maize yields from Western Kenya. - Kanyenji, George Magambo; Oluoch-Kosura,Willis; Onyango, Cecilia Moraa; Karanja Ng'ang'a, Stanley (African Association of Agricultural Economists, 2019)
Soil carbon enhancing practices (SCEPs) have been proven to be low-cost solutions in enhancing agricultural productivity and alleviate the detrimental effects of climate change. These practices can be adopted as complementary or as substitute practices due to their associated ecological benefits and cost. In view of this, there is limited literature on the impact of adopting a combination of SCEPs since their effect may be lower or higher than individual technologies. A structured survey was utilized to collect data from 334 households in Western Kenya. The study utilized the multinomial endogenous treatment effect model to assess the determinants and impact of adopting on maize yield. The results reveal that adoption is influenced by plots specific characteristics (distance to the plot and tenure system), external support factors (access to credit and farmers participation in markets), tropical livestock units and literacy level. In addition, the results showed that adoption of farmyard manure, intercropping, and intercropping and farmyard manure combination has a significant and positive impact on maize yield. This implies that there is a need to promote SCEPs adoption among smallholder farmers given its positive impact and associated low cost of implementation